2018
DOI: 10.1177/0263617418772660
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive hydrogen chloride and combined hydrogen chloride–hydrogen sulphide removal from biogas for solid oxide fuel cell application

Abstract: In order to reduce the toxic effect on solid oxide fuel cells performance caused by biogas contaminated with hydrogen chloride and hydrogen sulphide, the purification of biogas is essential. Adsorptive gas purification is a highly auspicious technology to provide pollution-free biogas for solid oxide fuel cell-based power units. In this work the authors examined the influence of different parameters onto the adsorption capacity of three commercially available sorbents. Experimental runs in a laboratory glass d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Weinlaender et al [108] demonstrated that an increase of HCl concentration in the inlet stream allows achieving a 15% higher sorbent uptake; achieved because of the increased concentration gradient, which is a driving force of adsorptive separation. Moreover, the test run time was reduced by a factor of 10 when the inlet concentration of HCl was increased by a factor 10.…”
Section: High Temperature Secondary Methods For Hcl Removalmentioning
confidence: 99%
“…Weinlaender et al [108] demonstrated that an increase of HCl concentration in the inlet stream allows achieving a 15% higher sorbent uptake; achieved because of the increased concentration gradient, which is a driving force of adsorptive separation. Moreover, the test run time was reduced by a factor of 10 when the inlet concentration of HCl was increased by a factor 10.…”
Section: High Temperature Secondary Methods For Hcl Removalmentioning
confidence: 99%